DISCURSIVE STRATEGIES IN ENGLISH ISLAMIC SERMONS - Rashidova Dilnoza (Western European Studies, 2025)
This study provides a comprehensive linguistic analysis of discursive strategies employed in English Islamic sermons. Using a corpus of 15 sermons and podcast episodes from prominent scholars such as Yasir Qadhi, Mufti Menk, and Hamza Yusuf (2020–2024), the research investigates lexical, syntactic, pragmatic, and stylistic levels of discourse. Frequency analysis of key linguistic terms is conducted to identify patterns of usage, while examples are analyzed to illustrate the discursive mechanisms that create semantic, pragmatic, and emotional impact. The findings indicate that these strategies are systematically organized to enhance communicative effectiveness, cohesion, and persuasive force in religious discourse
Keywords: cohesion; comprehensive; pragmatic; lexical